A systematic review and meta‐analyses of the association between 4 mycoplasma species and lower respiratory tract disease in dogs - Anisha Jambhekar; Elisabeth Robin; Kevin Le Boedec (Journal of Veterinary Internal Medicine, 2019)
Abstract Background The pathogenic role of mycoplasmas in the lower respiratory tract (LRT) of dogs is debated, because mycoplasmas can be isolated from both healthy and sick dogs. Objectives To critically assess available data from controlled observational studies on the role of 4 mycoplasma species in LRT disease of dogs. Design Systematic review and meta‐analyses. Methods Seven electronic databases were searched for relevant publications. Risk of bias was assessed by the Newcastle‐Ottawa Scale. Meta‐analyses, stratified by mycoplasmal species, were performed using a random effects Bayesian model with noninformative priors to estimate pooled odds ratios (ORs) and 95% confidence intervals (CIs) for the association between Mycoplasma cynos, Mycoplasma canis, Mycoplasma spumans, and Mycoplasma edwardii and LRT disease in dogs. Results Five studies were included from 1201 references identified. All studies dealt with M. cynos, whereas 3 dealt with the other mycoplasma species. A significant association was found between M. cynos and LRT disease (Bayesian OR, 3.60; CI, 1.31‐10.29). Conversely, M. canis, M. spumans, and M. edwardii were not significantly associated with LRT signs (Bayesian OR, 1.06; CI, 0.10‐14.63; Bayesian OR, 3.40; CI, 0.16‐54.27; and Bayesian OR, 1.04; CI, 0.05‐23.54, respectively). Conclusions and Clinical Importance Results support a pathogenic role of M. cynos and a commensal role of M. canis and M. edwardii in LRT in dogs. Although the association was not significant based on the CI, the point estimate of the Bayesian OR was relatively high for M. spumans, making its role less clear. Mycoplasma cynos‐specific polymerase chain reaction should be considered on samples from dogs with LRT.